English: English - Sitepu, Radiah; Purwanti, Ipung Fitri (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2026)
Copper contamination from anthropogenic activities negatively impacts water quality and agriculture, with documented cases showing reduced crop yields and economic losses. This study conducted a preliminary screening to evaluate the survivability and toxicity signs of V. zizanioides under copper exposure as an initial assessment of its potential for phytoremediation. A range finding test was performed using five Cu concentration (100, 250, 500, 750, 1000 mg/L) and control. Following 40 days-propagation period, plants were exposed to Cu for 7-14 days. Daily observations included plant condition and height, while pH and temperature were periodically monitored to ensure that plant mortality resulted from toxicity rather than environmental factors. The results indicated that V. zizanioides tolerated copper concentration up to 100 mg/L. However at concentrations above 100 mg/L, typical toxicity symptoms, such as chlorosis and necrosis, appeared as early as the second day. Complete plant mortality was observed at the highest concentration, 1000 mg/L. Although this study did not assess metal removal performance, these findings highlight the resilience of V. zizanioides under copper stress and provide an important basis for future research to determine its suitability for phytoremediation or constructed wetlands.